This machine still kills fascists : lyrics of Woody Guthrie [compact disc] - Guthrie, Woody, 1912-1967 (Dummy Luck Music, 2022)
Dropkick Murphys history with Woody Guthrie dates back decades, from covering "Gonna Be A Blackout Tonight" on their 2003 album Blackout, to using some of Guthrie's writing about Boston in their immortal hit "I'm Shipping Up To Boston". But on their latest album, This Machine Still Kills Fascists, Dropkick Murphys have crafted an entire record around the seminal American folk icon, bringing Woody Guthrie's perennial jabs at life-many of which are from the 1940s and '50s-into the present, with the resulting music eerily relevant to today's world. The idea for the collaboration had been percolating between Guthrie's daughter Nora and the band for more than a decade, with Nora curating a collection of her father's never before-published lyrics for the band over the years. The result is one of Dropkick Murphys most unique releases, and the culmination of two like-minded rebellious artists collaborating, albeit nearly a century apart.